Web3 : charting the Internet's next economic and cultural frontier - Tapscott, Alex (Harper Business, an imprint of HarperCollins Publishers, 2023)
"The coauthor of Blockchain Revolution presents a cutting-edge guide to the Internet's next era, covering everything from the metaverse and NFTs to decentralized finance and self-sovereign identity"--